Pertanggung Jawaban Pidana Terhadap Kapal Ikan dalam Negeri yang Tidak Memenuhi Standar Keselamatan Berlayar - Rio Herdy Saputra; Dinda Anisa Septiani Putri; Riska Ayu Sekarsari; Adrian Yan Permana; Masitha Tismananda Kumala (Presidensial: Jurnal Hukum, Administrasi Negara, dan Kebijakan Publik, 2026)
In Indonesia, maritime safety remains a problem. Ship captains and ship owners often disregard maritime safety standards, particularly for fishing vessels. Provisions for criminal liability for domestic fishing vessels that fail to meet maritime safety standards are an important legal instrument for regulating and enforcing maritime safety regulations in the fisheries sector. Failure of vessels to comply with safety requirements, such as the completeness of safety equipment, engine condition, and vessel structure, can potentially lead to accidents that endanger the lives of crew members and negatively impact the marine environment. This study uses a normative research method with a legislative approach. This article focuses on examining aspects of criminal liability, including the subjects, objects, and legal sanctions imposed for violations of maritime safety standards. The results indicate that perpetrators of violations can be subject to criminal sanctions in the form of fines, detention, and even revocation of vessel operating permits, taking into account human rights and environmental protection. Effective and synergistic law enforcement between relevant authorities is essential to provide a deterrent effect, encourage compliance with safety standards, and improve the system for the sustainability of marine resources.